2014
DOI: 10.1080/13102818.2014.969918
|View full text |Cite
|
Sign up to set email alerts
|

Selected adjunct cultures remarkably increase the content of bioactive peptides in Bulgarian white brined cheese

Abstract: Some lactic acid bacteria strains in milk media are capable of releasing bioactive peptides. In this study, we evaluated the angiotensin-converting enzyme (ACE)inhibitory activity of 180 lactic acid bacteria and selected several Lactobacillus helveticus, L. delbrueckii subsp. bulgaricus and L. casei strains that demonstrated strong ACE-inhibitory activity. The aim was to carry out a molecular study on the bioactive peptides released by the strains with the best ACE-inhibitory properties and by the strains demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 12 publications
(10 reference statements)
0
7
0
Order By: Relevance
“…Some of the peptides produced by LAB are known as phospho-peptides. They accelerate the mineral absorption of calcium, phosphorous, iron, and magnesium [67]. Different studies show a link between dairy intake and bone turnover markers and a positive association with bone mineral content.…”
Section: Bioactive Peptidesmentioning
confidence: 99%
“…Some of the peptides produced by LAB are known as phospho-peptides. They accelerate the mineral absorption of calcium, phosphorous, iron, and magnesium [67]. Different studies show a link between dairy intake and bone turnover markers and a positive association with bone mineral content.…”
Section: Bioactive Peptidesmentioning
confidence: 99%
“…Besides anti-hypertensive properties, ACE-I inhibition is also reported to have a favorable effect on other regulatory systems involved in modulating blood pressure, immune defense, diabetes and nervous system activities. 144 ACE-I inhibitors with a sulphydryl group are reported to show improved insulin sensitivity in vivo by modifying the actions of bradykinin. 145 Bradykinin has been reported to enhance glucose uptake in vivo and in vitro by enhancing insulin receptor phosphorylation.…”
Section: Functional Properties Ace Inhibitory Activitymentioning
confidence: 99%
“…They showed that the use of adjunct cultures in this type of cheese increases ACE-inhibitory activity until the 60th day of ripening. Dimitrov et al (2015) used different adjunct cultures in Bulgarian cheese to investigate ACE-inhibitory activity. They found that most inhibitory activity generated by L. helveticus A1, which releases the peptide Ala-Leu-Pro-Met as primary ACE inhibitor.…”
Section: Introductionmentioning
confidence: 99%